2008
DOI: 10.1073/pnas.0712278105
|View full text |Cite
|
Sign up to set email alerts
|

The PD-1/PD-L1 complex resembles the antigen-binding Fv domains of antibodies and T cell receptors

Abstract: coreceptor ͉ costimulation ͉ inhibitory receptor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
366
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(381 citation statements)
references
References 33 publications
(38 reference statements)
11
366
1
3
Order By: Relevance
“…To design the initial, "first-generation" library, we studied the crystal structure of the complex between murine PD-1 (mPD-1) and human PD-L1 (hPD-L1) (19) and identified 22 corresponding residues in human PD-1 (hPD-1) at the contact interface with PD-L1 for randomization (Fig. 1A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To design the initial, "first-generation" library, we studied the crystal structure of the complex between murine PD-1 (mPD-1) and human PD-L1 (hPD-L1) (19) and identified 22 corresponding residues in human PD-1 (hPD-1) at the contact interface with PD-L1 for randomization (Fig. 1A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2A). Previous studies identified several human PD-1 residues as critical for PD-L1 and PD-L2 binding (31)(32)(33)(34), and these residues are contained within the two sequences (Supplementary Fig. S2B).…”
Section: Binding Analysis Of Nivolumab and Inhibition Of Ligand Bindingmentioning
confidence: 99%
“…In contrast, the IgV and IgC domains of PD-L1 are in a straight line when complexed with PD-1 but diverge 38°from straight without PD-1 (5). This flexibility between the two domains suggests PD-L1 may accommodate to the orientation of receptor during binding (5). An unanswered question is how binding of ligand transduces a signal.…”
mentioning
confidence: 96%
“…B7-1 is a rigid rod with a very similar structure alone or bound to CTLA4 (11,12). In contrast, the IgV and IgC domains of PD-L1 are in a straight line when complexed with PD-1 but diverge 38°from straight without PD-1 (5). This flexibility between the two domains suggests PD-L1 may accommodate to the orientation of receptor during binding (5).…”
mentioning
confidence: 99%